In ovulo rescue of hybrid embryos in flame seedless grapes - influence of pre-bloom sprays of benzyladenine - Bharathy, P. V.; Karibasappa, G. S.; Patil, S. G.; Agrawal, Dinesh C. (Scientia Horticulturae, 2005)
Based on the theory that cytokinins are known to increase the sink strength of seeds for assimilates, the present investigation was carried out to study the influence of pre-bloom and bloom time sprays of benzyladenine (BA) on embryo recovery, germination and plant development in Flame Seedless grape variety by using in ovulo rescue methods. The combined effect of pollen parent type and sprays of BA drastically improved these parameters and the embryo recovery was more than doubled in all the crosses, except in cross FS x Concord. Also, germination of embryos was higher when BA sprays were given. Recovery of embryos and growth depended on BA treatment and the pollen parent types. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: benzyladenine; flame seedless; in ovulo embryo rescue; interspecific hybridization; Vitis spp.

Insights into the unfolding pathway and identification of thermally sensitive regions of phytase from aspergillus niger by molecular dynamics simulations - Kumar, Kapil; Patel, Krunal; Agrawal, Dinesh C.; Khire, Jayant Malhar (Journal of Molecular Modeling, 2015)
Thermal stability is of great importance in the application of commercial phytases. Phytase A (PhyA) is a monomeric protein comprising twelve alpha-helices and ten beta-sheets. Comparative molecular dynamics (MD) simulations (at 310, 350, 400, and 500 K) revealed that the thermal stability of PhyA from Aspergillus niger (A. niger) is associated with its conformational rigidity. The most thermally sensitive regions were identified as loops 8 (residues 83-106), 10 (161174), 14 (224-230), 17 (306-331), and 24 (442-444), which are present on the surface of the protein. It was observed that solvent-exposed loops denature before or show higher flexibility than buried residues. We observed that PhyA begins to unfold at loops 8 and 14, which further extends to loop 24 at the C-terminus. The intense movement of loop 8 causes the helix H2 and beta-sheet B3 to fluctuate at high temperature. The high flexibility of the H2, H10, and H12 helices at high temperature resulted in complete denaturation. The high mobility of loop 14 easily transfers to the adjacent helices H7, H8, and H9, which fluctuate and partially unfold at high temperature (500 K). It was also observed that the salt bridges Asp110-Lys149, Asp205-Lys277, Asp335-Arg136, Asp416-Arg420, and Glu387-Arg400 are important influences on the structural stability but not the thermostability, as the lengths of these salt bridges did not increase with rising temperature. The salt bridges Glu125-Arg163, Asp299-Arg136, Asp266-Arg219, Asp339-Lys278, Asp335-Arg136, and Asp424-Arg428 are all important for thermostability, as the lengths of these bridges increased dramatically with increasing temperature. Here, for the first time, we have computationally identified the thermolabile regions of PhyA, and this information could be used to engineer novel thermostable phytases. Numerous homologous phytases of fungal as well as bacterial origin are known, and these homologs show high sequence similarity. Our findings could prove useful in attempts to increase the thermostability of homologous phytases via protein engineering.
Keywords: Conformational dynamics; Molecular dynamics simulations; PhytaseA; Structurally weak regions; Thermostability